Deconstructing Antisocial Personality Disorder - Jones, Gayle (New Zealand Sociology, 2023)
Taking a social constructionist approach, this article critically examines antisocial personality disorder (ASPD) to investigate how a mental illness with vague diagnostic criteria and a lack of solid empirical backing continues to persevere within the mental health system. It explores the sociohistorical roots of ASPD in the nineteenth century, emerging with psychiatry’s interest in the moral transgressions of criminals as signs of mental disorder. This analysis then discusses the evolution of the ASPD label through the various iterations of the American Psychiatric Association’s Diagnostic and statistical manual of mental disorders in the twentieth century, to the contemporary moment where the current classification lists criteria that can be potentially applied to almost all of those who encounter the criminal justice system. Rather than being a legitimate mental disorder, it is concluded that the ASPD classification serves as a way for psychiatry to expand their expertise and influence beyond the psychiatric institution and further into the criminal justice system.